Measuring real-time blood viscosity with a ventricular assist device. (May 2019) - Hijikata, Wataru; Maruyama, Takuro; Suzumori, Yuki; Shinshi, Tadahiko
Ventricular assist devices assist in blood circulation and form a crucial component of artificial hearts. While it is important to measure parameters such as the flow rate, pressure head and viscosity of the blood, implanting additional devices to do such measurements is inadvisable. To this end, we demonstrate the adaptation of a ventricular assist device for the purpose of measuring blood viscosity. Such an approach eliminates the need for additional dedicated viscometers in artificial hearts. In the proposed method, the blood viscosity is measured by applying radial vibrational excitation to the impeller in a ventricular assist device using its magnetic levitation system. During the measurement, blood is exposed to a combination of a low shear rate (≈100/s) generated by the radial vibration of the impeller and a high shear rate (>10, 000/s) generated by the impeller's rotation. The apparent viscosity of blood depends on the shear rate, so we determined which shear rate was the dominant one in the proposed method. The measurement results showed that the viscosity measured by the proposed method was in good agreement with the reference viscosity measured with a high shear rate. The mean absolute deviation in the measurements using the proposed method and those obtained using a concentric cylindrical viscometer at a high shear rate was 0.12 mPa s for four samples of porcine blood, with viscosities ranging from 2.32 to 2.75 mPa s.